2021
DOI: 10.7150/jca.50255
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the CtBP1-FOXM1 transcriptional complex with small molecules to overcome MDR1-mediated chemoresistance in osteosarcoma cancer stem cells

Abstract: Chemoresistance is a major barrier for the chemotherapy of osteosarcoma. The induction of multidrug resistance protein 1 (MDR1), an ATP-dependent transporter, can efflux anti-cancer drugs, thereby decreasing chemosensitivity. However, an actual involvement of MDR1 in the chemoresistance of osteosarcoma cells has not been established. We obtained two cisplatin (CDDP)-resistant osteosarcoma cancer stem cell (CSC) lines using sphere formation medium supplemented with CDDP. These two CDDP-resistant CSC cell lines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…RAD51 is a protein observed in different types of cells, such as those of ovarian, colorectal and breast cancer, and its expression is key in the process of homologous recombination, which is one of the major mechanisms of the DNA damage response ( 29 ). When DNA damage occurs, RAD51 forms nucleofilaments with other repair proteins, such as BRCA2 and partner and localizer of BRCA2, on single-stranded DNA to facilitate homologous strand pairing and strand exchange during the DNA damage repair process ( 30 , 31 ). RAD51 has been reported to enhance the occurrence and development of colon cancer ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RAD51 is a protein observed in different types of cells, such as those of ovarian, colorectal and breast cancer, and its expression is key in the process of homologous recombination, which is one of the major mechanisms of the DNA damage response ( 29 ). When DNA damage occurs, RAD51 forms nucleofilaments with other repair proteins, such as BRCA2 and partner and localizer of BRCA2, on single-stranded DNA to facilitate homologous strand pairing and strand exchange during the DNA damage repair process ( 30 , 31 ). RAD51 has been reported to enhance the occurrence and development of colon cancer ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a transcription factor, CTBP1 serves a crucial role in regulating cell proliferation and apoptosis in different types of cells, such as breast cancer, osteosarcoma and ovarian cancer (14,(30)(31)(32). Furthermore, CTBP1 enhances the occurrence and development of different types of cancer (26).…”
Section: Discussionmentioning
confidence: 99%
“…Published data have shown that acquirement of cancer stemness was associated with MDR and its related adverse prognosis. 6,[16][17][18] As a typical protein for MDR, the expression of multidrug transporter P-glycoprotein (P-gp), an ATP-binding cassette (ABC) transporter protein encoded by the MDR1 has been identified as a crucial regulator for clinical MDR and stemness in cervical cancer. 5,6 Similar to the inhibitory role of PDCD4 in cancer cell growth, proliferation, migration, invasion, and carcinogenesis, [19][20][21][22][23] we specifically found that the reduced PDCD4 induced the acquirement of cancer stemness, resulting in the increased cisplatin resistance on cervical cancer, which was related to the increase in MDR1 expression of cervical cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Oct4 knockdown with siRNA induced a significant decrease in cell proliferation, invasion, and apoptosis [76] . TBL1XR1 is a transcriptional co-factor which is overexpressed in osteosarcoma patients [77] . Its overexpression in MG63 and U2-OS cell lines induced a CSC phenotype in contrast to its repression.…”
Section: Molecular Regulation Of Cancer Stem-like Cells In Osteosarcomamentioning
confidence: 99%
“…Its overexpression in MG63 and U2-OS cell lines induced a CSC phenotype in contrast to its repression. TBL1XR1 thus provides osteosarcoma cells with tumorigenic properties and promotes the recurrence of osteosarcoma in a STAT-3 signaling dependent manner [77] . Transcriptional complexes can also modulate osteosarcoma drug resistance.…”
Section: Molecular Regulation Of Cancer Stem-like Cells In Osteosarcomamentioning
confidence: 99%